Blockade of costimulatory CD27/CD70 pathway promotes corneal allograft survival. (October 2020) - Narimatsu, Akitomo; Hattori, Takaaki; Usui, Yoshihiko; Ueno, Hiroki; Funaki, Toshinari; Komatsu, Hiroyuki; Nakagawa, Hayate; Akiba, Hisaya; Goto, Hiroshi
Abstract: Purpose: To determine whether the CD27/CD70 pathway plays a significant role in corneal allograft rejection by investigating the effect of blocking the CD27/CD70 pathway by anti-CD70 antibody on corneal allograft survival. Methods: Orthotopic penetrating keratoplasty was performed using C57BL/6 donor grafts and BALB/c recipients. Expression of CD27 and CD70 on rejected cornea was examined by immunohistochemistry. Corneal transplant recipients received intraperitoneal injection of anti-CD70 antibody (FR70) or control rat IgG. Alloreactivity was measured by mixed lymphoid reaction (MLR) in recipients administered control rat IgG and those administered anti-CD70 antibody. Corneal expression of IFN-γ and IL-12 was also examined in both groups. Graft opacity was assessed over an 8-week period and graft survival was evaluated using Kaplan-Meier survival curves. Proportion of CD4 + CD44 + memory T cells in lymph nodes was measured by flow cytometry. Results: CD4 + CD27 + cells and CD11c + CD70 + cells were present in rejected cornea. Anti-CD70 antibody administration suppressed alloreactivity in corneal allograft recipients, and inhibited IFN-γ expression in recipient cornea ( p  < 0.05). Anti-CD70 antibody suppressed opacity score of recipient cornea and prolonged corneal allograft survival ( p  < 0.05). Proportion of CD4 + CD44 + memory T cells in recipient lymph nodes was reduced by anti-CD70 antibody treatment. Conclusion: The CD27/CD70 pathway plays a significant role in corneal allograft rejection by initiating alloreactive Th1 cells and preserving memory T cells. Anti-CD70 antibody administration prolongs corneal allograft survival indicating the potential therapeutic effect of CD27/CD70 pathway blockade on corneal allograft rejection. Higlights: CD27 and CD70 were expressed in the rejected cornea. Anti-CD70 antibody reduced allogeneic T cell reaction and prolonged corneal allograft survival.